THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT PUBLIK SERVICE PERFORMANCE IN DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SULAWESI SELATAN - Zahra Galuh Fitria Rusmana; Didin Halim; Oky Nur Pratiwi Johansyah; Nina Agustina (Jurnal Aktor, 2026)
This study aims to determine the influence of Leadership Style and Work Environment on Public Service Performance at the Library and Archives Service of South Sulawesi Province. The type of research uses quantitative descriptive with data collection techniques using observation and questionnaires of 42 respondents with sampling techniques. Analyzed by multiple linear regression using SPSS version 25.Descriptive research results show that Leadership Style is classified as very good at 4.16, Work Environment is classified as very good at 4.08, Service Performance is classified as very good at 4.00, Inferentially Leadership Style has no influence on Service Performance. This shows that without supervision from leadership, service performance continues to run very well. There is an influence of the Work Environment on Service Performance of 0.47. There is a simultaneous influence between Leadership Style and Work Environment on Service Performance of 0.168. The ability of the independent variable to explain the Service Performance variable at the Library and Archives Service of South Sulawesi Province is simultaneously explained by Leadership Style and Work Environment on Service Performance by 46.3% while 53.7% is influenced by variables not examined in this research. Based on the research results, it was concluded that the independent variable that had the dominant influence was the work environment variable in influencing service performance compared to the leadership style variable. Service performance should be focused on the work environment in supporting Service Performance at the Library and Archives Service of South Sulawesi Province.